2022
DOI: 10.1055/s-0042-1749453
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Interventions for Asthma

Abstract: Exposure and sensitization to environmental factors play a fundamental role in asthma development and is strongly associated with asthma morbidity. While hereditary factors are critical determinants of asthma, exposures to environmental factors are implicated in the phenotypic expression of asthma and have been strongly associated in the risk of its development. Significant interest has thus been geared toward potentially modifiable environmental exposures which may lead to the development of asthma. Allergen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 173 publications
(325 reference statements)
0
2
0
Order By: Relevance
“…Tobacco smoke is one of the most potent exposures for asthma morbidity. Approximately 14% of children in the United States are exposed to second hand smoke at home; the incidence is higher in inner-city low-income households [6]. In cross-sectional reviews of subjects enrolled in the National Institutes of Health (NIH)/National Institutes of Allergy and Infectious Diseases-funded School Inner-City Asthma Study (SICAS), Ruran et al [7] observed higher urinary cotinine levels in children of lower income homes as well as non-White race and Hispanic or Latinx groups.…”
Section: Indoor Exposuresmentioning
confidence: 99%
“…Tobacco smoke is one of the most potent exposures for asthma morbidity. Approximately 14% of children in the United States are exposed to second hand smoke at home; the incidence is higher in inner-city low-income households [6]. In cross-sectional reviews of subjects enrolled in the National Institutes of Health (NIH)/National Institutes of Allergy and Infectious Diseases-funded School Inner-City Asthma Study (SICAS), Ruran et al [7] observed higher urinary cotinine levels in children of lower income homes as well as non-White race and Hispanic or Latinx groups.…”
Section: Indoor Exposuresmentioning
confidence: 99%
“…Second-hand tobacco smoke exposure is higher in inner-city low-income households [16]. Data from the school inner-city asthma study recently found children of lower income households, nonwhite race, and Hispanic ethnicity had higher urinary cotinine levels that were associated with worse asthma symptoms and increased exacerbations [17].…”
Section: Environmental Riskmentioning
confidence: 99%